Changes In the Reproductive System of Girls with Vitamin D Deficiency - Isroilova Guljannat Pardabayevna (Genius Publishing Group, 2022)
In order for the human body to function properly, well-coordinated work and interaction of all its systems is necessary. There are many components involved in the life support process. Destabilization of the amount of one of them threatens the development of serious ailments. Vitamin D deficiency is especially dangerous. Vitamin D deficiency can lead to serious violations of life support systems and pathologies of internal organs.
Keywords: Vitamin D; immune system; deficiency; reproductive function